Impact of Glutathione Administration on Antioxidant Levels and Ileum Histologic of Growth Phase of Cihateup Duck in Extensively Maintained - Andi Mushawwir; N. Suwarno; H.N. Aritonang (Jurnal Sain Peternakan Indonesia, 2022)
This research has been carried out for a month using eighty three-month-old female Cihateup ducks and has been used to study the influence of glutathione on the endogen antioxidant response and  histological illeum. The separation of glutathione was carried out using the distillation technique. Each experimental group consisted of 20 ducks, each treated with G0 = without glutathione; G1= Administration of glutathione 150 µL/head; G2 = Administration of glutathione 175 µL/head; G3= Administration of glutathione 175 µL/head. Tissue and blood sampling was collected at the end of the study by EDTA tube and a fixative solution, and tissue preparations were made using the Mallory-Asan technique and analyzed using a binocular microscope. Antioxidant levels were measured using a spectrophotometer technique based on the instructions of the Randox Kit. The results showed that glutathione affected (P<0.05) morphometric ileum (villi, Peyeri's plaque and goblet cells) and increased with increasing glutathione level and endogenous antioxidant response. It was concluded that glutathione is able to stimulate protein and lipid anabolism, as well as hormonal signals related to ileal tissue growth and antioxidants.